Thinking through our mothers and sisters: o problema da escrita feminina e da tradição na obra ensaística de Virginia Woolf - Silva, Josenildo Ferreira Teófilo da (2024)
This research aims at discussing through an analysis of Virginia Woolf’s (1882-1941) essayistic oeuvre some of the main causes that led women to be silenced or even erased by a literary historiography largely dominated by a hegemonic patriarchal discourse. As a result, these women ended up assuming a position of subalternity in relation to an essentially male canon, which generally relegated them to a peripheral space, in other words, to the margins of a system that viewed these women’s attempts to establish themselves as professional writers with a certain amount of suspicion and indifference. Our intention consists of discussing the various paths that Virginia Woolf proposes for this woman novelist in her struggle for economic and intellectual freedom, thus breaking with the obstacles and deprivations instituted by an excessively “masculine” sentence, full of hatred and resentment. Based on the reading of important essays and reviews produced by the author throughout her career as a literary critic, we seek to establish a dialogue between her political and artistic project, reflecting on the foundations of Virginia Woolf’s humanist feminism, especially with regard to her theory of the so-called “androgynous mind”, i.e. a mind in which masculine and feminine cooperate with each other in perfect harmony and balance. To this end, we draw on the discussions presented by T. S. Eliot (1919), Sandra Gilbert and Susan Gubar (1985), on the concept of tradition and parental inheritance in the novel; Elaine Showalter (1981) and Herbert Marder (1968), on the question of feminist criticism in Virginia Woolf; and, in particular, Hélène Cixous (2002), with her concept of écriture féminine explored in her essay The Laughter of Medusa.